Peramalan Produksi Pulp Menggunakan ARIMA dan Analisis Daya Saingnya di Pasar Internasional - Maria Arista Ulfa; Isna Ayu Safitri Kusuma Dewi; Yusuf Darmawan (EKONOMI DAN BISNIS DIGITAL, 2023)
The industrial sector is currently one of the largest contributing sectors to Indonesia's Gross Domestic Product (GDP). One of the industries that has contributed is the industry that produces processed wood products and their derivatives such as pulp, paper, blockboard, wood pellets, plywood and various types of furniture. Pulp usually comes from wood fiber and is used as a raw material for making paper which currently has strong competitiveness in the global market. This condition makes Indonesia's opportunities in the pulp trade still wide open, so that forecasting of pulp production is carried out as information in terms of quantity in an effort to increase competitiveness in the world market. Based on the results of forecasting using ARIMA, the MAD value is 125845.163, MSE is 18630880176.774 and MAPE is 17.81. While the analysis results obtained using the Trade Specialization Index (ISP) and Acceleration Ratio (AR) have values that tend to be positive with an average value of 0.1164353 and 1.31709576